MODEL PENGEMBANGAN SUMBER DAYA MANUSIA DI LEMBAGA PENDIDIKAN ISLAM - Ino Bachtryanto; Pardiman Pardiman; Ridwan Basalamah (Reflektika, 2021)
This article discusses the procedure for diagnosing capabilities in a knowledge-based organizational capability development model. This research uses library research. In this study, researchers used two kinds of data, namely primary data and secondary data. The method of data collection is by tracing sources of literature documentation and library materials that are relevant to the problems studied. The results of the analysis conclude that staff development is an increase in intellectual or emotional abilities needed to do a better job with the principles of growth, change, and reform. Staff development constraints include participants, trainers or infrastructure, development facilities, curriculum, and development funds. An effective staff development model begins with human resource planning, identifying the required capabilities and capacities, Succession Planning, Development Needs Assessment, Development Planning, Development Approach, and Evaluation of Development Success.